Population-wide persistent hemostatic changes after vaccination with ChAdOx1-S - de Laat, Bas; Stragier, Hendrik; de Laat-Kremers, Romy; Ninivaggi, Marisa; Mesotten, Dieter; Thiessen, Steven; Van Pelt, Kristien; Roest, Mark; Penders, Joris; Vanelderen, Pascal; Huskens, Dana; De Jongh, Raf; et al. (Frontiers in Cardiovascular Medicine, 2022)
Various vaccines were developed to reduce the spread of the Severe Acute Respiratory Syndrome Cov-2 (SARS-CoV-2) virus. Quickly after the start of vaccination, reports emerged that anti-SARS-CoV-2 vaccines, including ChAdOx1-S, could be associated with an increased risk of thrombosis. We investigated the hemostatic changes after ChAdOx1-S vaccination in 631 health care workers. Blood samples were collected 32 days on average after the second ChAdOx1-S vaccination, to evaluate hemostatic markers such as D-dimer, fibrinogen, α2-macroglobulin, FVIII and thrombin generation. Endothelial function was assessed by measuring Von Willebrand Factor (VWF) and active VWF. IL-6 and IL-10 were measured to study the activation of the immune system. Additionally, SARS-CoV-2 anti-nucleoside and anti-spike protein antibody titers were determined. Prothrombin and fibrinogen levels were significantly reduced after vaccination (−7.5% and −16.9%, p < 0.0001). Significantly more vaccinated subjects were outside the normal range compared to controls for prothrombin (42.1% vs. 26.4%, p = 0.026) and antithrombin (23.9% vs. 3.6%, p = 0.0010). Thrombin generation indicated a more procoagulant profile, characterized by a significantly shortened lag time (−11.3%, p < 0.0001) and time-to-peak (−13.0% and p < 0.0001) and an increased peak height (32.6%, p = 0.0015) in vaccinated subjects compared to unvaccinated controls. Increased VWF (+39.5%, p < 0.0001) and active VWF levels (+24.1 %, p < 0.0001) pointed toward endothelial activation, and IL-10 levels were significantly increased (9.29 pg/mL vs. 2.43 pg/mL, p = 0.032). The persistent increase of IL-10 indicates that the immune system remains active after ChAdOx1-S vaccination. This could trigger a pathophysiological mechanism causing an increased thrombin generation profile and vascular endothelial activation, which could subsequently result in and increased risk of thrombotic events.